An intensive professional development in family child care: a promising approach. Issue 2 (3rd April 2021) - Han, Myae; Buell, Martha; Hallam, Rena; Hooper, Alison
ABSTRACT: The quality of early care and education affects a wide range of children's experiences and developmental outcomes. Family Child Care (FCC) is no exception, and attention to increasing the quality of Family Child Care is needed. The purpose of the current study was to examine an experimental case of intensive Professional Development (PD) in FCC programmes focusing on domain-specific quality (language and literacy) and global quality. Forty-nine FCC providers in two states participated in the study. Thirty-eight FCC providers received intensive PD support, including five three-hour training workshops on early language and literacy, weekly onsite technical assistance, and monthly Community of Practice meetings. Eleven FCC providers served as a comparison group. The Child/Home Environmental Language and Literacy Observation (CHELLO) and Family Child Care Environmental Rating Scale (FCCERS-R) were used to measure the quality of FCC. Results showed significant improvement in the high-intensity PD group on both measures. The study presents a promising model of PD that may be an appropriate approach to embed within Quality Rating and Improvement Systems (QRIS) in early child care and education.